Effects of Myrtus communis L. Extract and Apocynin on Lens Oxidative Damage and Boron Levels in Rats with a High Fat-Diet - ERCAN, FERİHA (My University, 2021)
Objectives: Nutritional obesity causes oxidant damage in the body and cataract formation in the lenses by increasing the formation of free radicals. Myrtus communis leaf extracts (Myr) have antioxidant properties, and apocynin (Apo) is an effective NADPH-oxidase inhibitor. The data on tissue boron levels are quite lacking. The aim of this novel study was to investigate the effects of Myr and Apo treatment on boron levels and oxidative lens damage in rats fed a high-fat diet (HFD). Materials and Methods: Wistar albino male rats were randomly divided into four groups: the control group, HFD group, HFD + Myr group, and HFD + Apo group. Body weight and blood lipids were determined before and after the experiment. After decapitating the rats, the lenses were removed and homogenized. Catalase (CAT) and superoxide dismutase (SOD) activities and boron, malondialdehyde (MDA), and reduced glutathione (GSH) levels in the lens homogenates were determined. Results: The HFD increased serum triglyceride (p<0.05), total cholesterol level (p<0.001), body weight (p<0.001), and lens MDA levels (p<0.01) and decreased lens GSH (p<0.05) and boron level (p<0.01), SOD (p<0.001), and CAT activity (p<0.001). However, Myr and Apo treatment reduced the rats' body weight (p<0.001), serum triglyceride (p<0.05), and total cholesterol level (p<0.001) and increased lens boron (p<0.01; p<0.001), GSH levels (p<0.05; p<0.01), and CAT activity (p<0.001). Conclusion: Both Myr and Apo may be able to reduce oxidative stress in the lenses of obese rats caused by HFD by increasing boron levels.
Keywords: Obesity; apocynin; antioxidants; Myrtus communis; boron; lens